2.4mm Non-Cannulated Screws are Non-Inferior to 4.0mm Cannulated Screws for Medial Malleolar Fixation in Unstable Ankle Fractures. Issue 4 (22nd October 2020) - Fram, Brianna R.; Schmitz, Joseph L.; Rogero, Ryan G.; Chang, Gerard; Krieg, James
Category: Ankle; Trauma Introduction/Purpose: Ankles fractures are the third most common adult fractures, representing significant cost to society. This makes the effectiveness of ankle open reduction internal fixation (ORIF) an important area for study. The majority of existing literature on medial malleolus fracture fixation involves biomechanical testing in synthetic bone or cadaveric models. We sought to compare the clinical efficacy of medial malleolar fixation with 2.4mm non-cannulated screws to 4.0mm cannulated screws by evaluating rates of loss of reduction and hardware failure. Methods: We performed a propensity-score-matched retrospective cohort study on patients who underwent ORIF of an unstable ankle fracture with fixation of the medial malleolus with either 2.4mm non-cannulated (N=51 ankles in 51 patients) or 4.0mm cannulated (N=60 ankles in 60 patients) screws. Vertically oriented medial malleolus fractures or those in which additional fixation was used were excluded. We identified post-operative complications and compared follow-up radiographs with immediate post-operative radiographs for signs of hardware failure or loss of reduction. Mean age was 50.2 years (SD 13.9). There was no significant difference between groups in age, BMI, Charleston Comorbidity Index (CCI), smoking or diabetes status. The 2.4mm patients were more likely to require syndesmosis fixation (56.9% 2.4mm, 30.0% 4.0mm, p=0.007) but not posterior malleolus fixation (25.5% 2.4mm, 28.3% 4.0mm, p=0.831). Most medial malleoli were fixed with 2 screws (1 screw 9.8%, 2 screws 90.2% 2.4mm, 1 screw 7.0%, 2 screws 93.0% 4.0mm, p=0.60). Results: There was no significant difference in total complications (7.8% 2.4mm, 15.0% 4.0mm, p=0.375), operative complications (5.9% 2.4mm, 5.0% 4.0mm, p=1.00), loss of medial reduction (3.9% 2.4mm, 6.7% 4.0mm, p=0.69), or medial hardware breakage (2.0% 2.4mm, 0% 4.0mm, p=0.45). The two patients in the 2.4mm screw group with loss of medial malleolus fixation were noncompliant with non-weight bearing restrictions and failed by screw backing out, while the 4 patients in the 4.0mm group failed by medial fracture fragment displacement around stable screws. The 4.0mm group had more nonoperative complications (0% 2.4mm, 10.0% 4.0mm, p=0.031); one of these was delayed union of the medial malleolus, while the remainder were delayed lateral wound healing or sural or superficial peroneal distribution paresthesias, which appeared unrelated to medial fixation type. Conclusion: When used for medial malleolus fixation in unstable ankle fractures, 2.4mm non-cannulated screws do not have higher rates of loss of reduction or hardware failure compared to 4.0mm cannulated screws. Given their decreased cost and equivalent ease of insertion, surgeons should consider their use when fixing unstable ankle fractures.